Nephropathy after long term lithium therapy – case report - Olajossy, Marcin; Bąk-Ponieważowicz, Ewa; Ponieważowicz, Artur (Current Problems of Psychiatry, 2012)
Lithium is widely used to treat bipolar disorder. The aim of the paper was to present a problem of lithium-induced nephropathy. The adverse renal effects of long term lithium therapy include nephrogenic diabetes insipidus,acute renal insufficiency and chronic renal disease. Screening test suggested to catch the beginning of renal function abnormalities in patients undergoing long-term lithium therapy are the analysis of urine (specific gravity, protein), serum creatinine, GFR, blood pressure, ultrasound / CT (renal microcysts). Our case study shows that a rapid increase of lithium level in the blood, despite use of the same dose is predictor of developing chronic kidney disease.